2020
DOI: 10.1371/journal.pone.0237775
|View full text |Cite|
|
Sign up to set email alerts
|

Diet type influences the gut microbiome and nutrient assimilation of Genetically Improved Farmed Tilapia (Oreochromis niloticus)

Abstract: Nile tilapia, Oreochromis niloticus is the third most commonly farmed finfish species in the world, accounting for nearly 5% of global aquaculture production. In the past few decades much of the success of this species has been attributed to the development and distribution of Genetically Improved Farmed Tilapia (GIFT). Despite the increasing availability of GIFT, the productivity of small-scale farming remains highly variable, particularly in developing nations. Commercial fish-feed pellets can increase fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 67 publications
0
27
0
Order By: Relevance
“…Diet is among the main factors affecting the structure and composition of the intestinal microbiota of genetically improved farmed tilapia [ 80 ]. To date, many nutritional factors reportedly affect the structure of host intestinal microbiota, including amino acid [ 81 ], fat [ 82 ], fructose, and glucose [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diet is among the main factors affecting the structure and composition of the intestinal microbiota of genetically improved farmed tilapia [ 80 ]. To date, many nutritional factors reportedly affect the structure of host intestinal microbiota, including amino acid [ 81 ], fat [ 82 ], fructose, and glucose [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gut bacterial communities of Nile tilapia larvae were significantly affected by the rearing environment (recirculating or active suspension systems) [ 42 ]. Diet type influences the diversity and difference of gut bacterial community of tilapia [ 57 , 58 ]. Moreover, a strong correlation between genotype and gut microbial assemblages in fish were reported recently [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this fish species, gut microbiome members play a pivotal role in supporting host physiology and health, through microbial-mediated functions involved in disease resistance, growth, and metabolism [21,22]. Recent genomic studies have revealed this commensal community in Nile tilapia to be influenced by a number of factors commonly associated with aquaculture husbandry practices, such as alternations in salinity [23], dietary changes [22,24], and starvation [25]. Likewise, a number of studies have demonstrated that this commensal community in Nile tilapia and other fish species can also be altered following exposure to a number of antibiotics, including OTC [13,17,26,27].…”
Section: Introductionmentioning
confidence: 99%